Analisis Penggunaan Jaringan Fiber Optik Untuk Jaringan Komunikasi Scada Di PT PLN UP3 Bekasi - Tiurma Pratiwi, Bella; Setyowati, Arum; Maruddani, Baso (PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA FAKULTAS TEKNIK UNIVERSITAS NEGERI JAKARTA, 2023)
This study aims to analyze fiber optic networks for SCADA communication networks. The method used takes into account variables such as signal quality, fiber optic attenuation, and interference data on fiber optic networks in SCADA communication systems. The device required in this study is an OTDR (Optical Time Domain Reflector). From the results of this study's analysis, the initial activation measurements still require repairs to the fiber optic cable at several points to meet the standards applied at PT. Indonesia Comnets Plus. On the DUrikosambi-Kembangan link, the measurement results after repairs using an OTDR have an average attenuation of 2.399 dB and an average attenuation value from the link power budget calculation of 4.673 dB. From the results of attenuation measurements using an OTDR on both links, there are differences in attenuation values ​​in each core, indicating a decrease in the quality of the link.